Female Circumcision in Bugis-Makassar Society of South Sulawesi: Between Cultural Symbolism and the Islamic Law - Basri, Rusdaya; Rahmawati, Rahmawati; Zainab, Zainab; Ali, Farouq Ahmad; Ameliah, Rizkah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
A clash of ideas between Islamic teachings and local traditions regarding female circumcision. Bugis women still practice circumcision as a mandatory rite. This research aimed to reveal female circumcision, community understanding, and maslahah contextualization of female circumcision in the traditions of the Bugis tribe in South Sulawesi. This research was field research with a legal culture and benefits approach. Symbolic interactionism theory was used as an analytical tool. The data collection was carried out using observation, interviews, and documentation methods using field studies. The data obtained was then processed and analyzed through three stages, namely data reduction (data selection), data presentation, and conclusions. The research results found that the Bugis female circumcision rite consisted of three stages, namely the preparation, implementation, and post-implementation stages. Bugis female circumcision had a symbolic meaning such as a symbol of Islamic teachings, glory and high rank, prosperity, harmonious family life, purity, and safety in this world and the hereafter. The maslahah assessment of the practice of Bugis female circumcision rites in South Sulawesi and West Sulawesi was studied from 2 benchmarks, namely based on the impact caused and based on the level of damage caused. The practice of symbolic circumcision was permitted and even recommended because it had maslahah value and the symbolic values contained in this practice can be a dzarai (intermediary) in obtaining benefits.